A logic gate for external regulation of photopolymerization. Issue 42 (6th September 2016) - Shanmugam, Sivaprakash; Xu, Jiangtao; Boyer, Cyrille
Abstract : The use of photocatalysts for visible light mediated reversible deactivation radical polymerization (RDRP) provides an efficient route for the synthesis of well-defined polymers with spatial, temporal and sequence control. Abstract : The use of photocatalysts for visible light mediated reversible deactivation radical polymerization (RDRP) provides an efficient route for the synthesis of well-defined polymers with spatial, temporal and sequence control. However, current techniques are often limited to the use of organic solvents with only few reports exploring polymerization in biologically relevant media, such as water. In addition, the use of photocatalysts to modulate polymerization rates by manipulating absorption wavelengths and intensity of light provides an additional layer of control over polymerization. By using a water soluble zinc porphyrin, Zn(ii ) meso -tetra (4-sulfonatophenyl) porphyrin (ZnTPPS 4− ), we were able to carry out successful photopolymerizations with various water soluble monomers in an aqueous environment. More interestingly, the pH of the polymerization mixtures affect the performance of the catalyst, where faster polymerization was observed in near-neutral and basic environments in comparison to an acidic environment. In the presence of low energy red light irradiation ( λ max = 635 nm, 0.828 mW cm −2 ), we were able to carry out successful RAFT photopolymerization, yielding polymers with well-defined molecular weights and molecular weight distributions that are as low as 1.07.